2021
DOI: 10.1016/j.chaos.2021.111275
|View full text |Cite
|
Sign up to set email alerts
|

A fractional-order model for CoViD-19 dynamics with reinfection and the importance of quarantine

Abstract: Coronavirus disease 2019 (CoViD-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Among many symptoms, cough, fever and tiredness are the most common. People over 60 years old and with associated comorbidities are most likely to develop a worsening health condition. This paper proposes a non-integer order model to describe the dynamics of CoViD-19 in a standard population. The model incorporates the reinfection rate in the individuals recovered from the diseas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The method we use, is a method that uses the same techniques as [37] whose standard error is given by the expression max j |y(t j ) − y j | = O(h 2 ), where h = max j (t j+1 − t j ) and t j ∈ [t 0 , t 0 + t ⋆ ] for some fixed t ⋆ > 0. The FracPECE method was already used by other authors in previous studies, such as [14,38].…”
Section: Numerical Simulations and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method we use, is a method that uses the same techniques as [37] whose standard error is given by the expression max j |y(t j ) − y j | = O(h 2 ), where h = max j (t j+1 − t j ) and t j ∈ [t 0 , t 0 + t ⋆ ] for some fixed t ⋆ > 0. The FracPECE method was already used by other authors in previous studies, such as [14,38].…”
Section: Numerical Simulations and Resultsmentioning
confidence: 99%
“…These models allow us to draw a lot of conclusions about how we should act in situations related to epidemics in different countries around the world. For example, these mathematical analysis could help in decision making by government leaders in combating possible economic losses that come from pandemic disasters, particularly due to SARS-CoV-2 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2020 ). The predictor-corrector regulation method arising from Adams-Bashford-Moulton type is utilized for the numerical solution of a fractional order CoViD-19 virus model expressing the dynamics of reinfection and the importance of quarantine (Maurício de Carvalho and Moreira-Pinto 2021 ). The optimal treatment problem is solved via the forward-backward iterative method for the combined antiretroviral drug therapy in an HIV infection model (Nath et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus has been included in recent studies on CoViD-19 [3,17,20]. Many studies have been conducted in the field of mathematics, and it has been shown that differential equations using fractional operators are effective in demonstrating epidemic models linked to many infectious illnesses [7,12].…”
Section: Introductionmentioning
confidence: 99%